Predictive Model for Positive Video Capsule Endoscopy in Iron Deficiency Anemia - Hamdeh, Shadi; Fathallah, Jihan; Zhang, Hui; Charoen, Amber; Altamimi, Barakat Aburajab; Odufalu, Florence-Damilola; Dave, Devashree; Sayed, Amer El; Glick, Laura R.; Grisolano, Scott; Hachem, Christine; Hammami, Muhammad Bader; et al. (Digestive diseases and sciences, 2023)
Background and Aims Bleeding from the gastrointestinal tract can contribute to the development of iron deficiency anemia (IDA) among individuals without another obvious source of bleeding. In order to identify patients most likely to benefit from examination of the small bowel, our aim was to create a risk score for positive video capsule endoscopy (VCE) in IDA utilizing a multicenter collection of studies. Methods We performed a retrospective multicenter study utilizing VCE studies performed for an indication of IDA between 1/1/2005 and 7/31/2018. VCE findings were graded based on the P0–P2 grading system. The primary outcome of interest was a positive (P2) VCE. Data were analyzed with Student’s t test for continuous variables and the Fisher’s exact test for categorical variables. Logistic regression was used to identify independent associations with positive VCE. Results In total, 765 VCE procedures were included with 355 (46.5%) male subjects and a median age of 63.2 (SD 15.3) years. One hundred ninety studies (24.8%) were positive (P2) for small bowel bleeding. Four variables associated with positive VCE which were incorporated into a point scoring system: (+) 1 for age ≥ 66 years, active smoking and cardiac arrythmia and (−) 1 for preceding hemoglobin level ≥ 8.5. The risk probabilities for positive VCE-assigned scores − 1, 0, 1, and 2 + were 12.3% (95% CI 7.3–17.3%), 20% (14.9–25.1%), 34.8% (28.6–41%), and 39% (30–47.8%). Conclusion In order to improve the diagnostic yield of capsule examinations, risk factors should be applied to clinical decision-making. We created a risk score for positive VCE in IDA, including the risk factors of age, smoking, history of cardiac arrythmia, and preceding hemoglobin level.